(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
The general and specific combining ability of sex promising cucumber lines in the diallel cross-breeding system of the World Vegetable Center was selected. The following quantitative characteristics were considered: the number of days before the disclosure of the female flowers, the number of days before the technical ripeness of the fruit, the number of fruits on one plant, the average weight of the fruit, the productivity of one plant. When comparing the varieties of SCA and GCA in cucumber samples according to the main economically valuable characteristics, it was found